CUSTOMER CITIZENSHIP BEHAVIOR ON BUSINESS PERFORMANCE: ARTIFICIAL INTELLIGENCE AS MODERATION IN SMES - Utama, Andyan; Shiratina, Aldina; Marlapa, Eri; Ali, Anees (Faculty of Economic and Business, University of Pasundan, 2025)
The purpose of this study is to analyze the influence of Customer Experience (CE) and Brand Commitment (BC) on Business Performance (BP) and to examine the mediating role of Customer Citizenship Behavior (CCB). The study also aims to evaluate the moderating role of Artificial Intelligence (AI) in the relationship between CE and BC with BP. This research employs a quantitative approach with a survey design. The sample consists of 150 MSMEs in Tasikmalaya City, analyzed using SEM-SmartPLS4. The findings reveal that CE and BC have a positive and significant effect on CCB and BP. Additionally, CCB has a positive and significant impact on BP and mediates the influence of CE and BC on BP. However, AI does not moderate the relationships between CE and BP or BC and BP.